Insight into luminescent properties, energy transfer and thermal stability of NaBa4(AlB4O9)2Cl3:Ce3+, Tb3+ phosphors. Issue 9 (2nd March 2019) - Zhang, Weilun; Liang, Yujun; Zhu, Yingli; Liu, Shiqi; Li, Haoran; Lei, Wen
Abstract: A series of Ce 3+ and Tb 3+ singly‐ and co‐doped NaBa4 (AlB4 O9 )2 Cl3 (NBAC) phosphors have been synthesized via high‐temperature solid state route. The crystal structure, morphology, photoluminescent properties, thermal properties and energy transfer process between Ce 3+ and Tb 3+ were systematically investigated. The structure refinements indicated that the phosphors based on NBAC crystallized in P 42 nm polar space group in monoclinic phase. The emission color could be tuned from blue (0.1595, 0.0955) to green (0.2689, 0.4334) via changing the ratio of Ce 3+ /Tb 3+ . The energy transfer mechanism of Ce 3+ /Tb 3+ was verified to be dipole–quadrupole interaction via the examination of decay times of Ce 3+ based on Dexter's theory. The good thermal stability showed the intensities of Ce 3+ at 150°C were about 66.9% and 64.88% in NBAC:0.09Ce 3+ and NBAC:0.09Ce 3+, 0.07Tb 3+ of that at room temperature, and the emission intensities of Tb 3+ remained 102.41% in NBAC:0.11Tb 3+ and 95.22% in NBAC:0.09Ce 3+, 0.07Tb 3+ due to the nephelauxetic shielding effect and the highly asymmetric rigid framework structure of NBAC. The maximum external quantum efficiency (EQE) of Ce 3+ in NBAC:0.09Ce 3+, y Tb 3+ phosphors could reach 43.38% at y = 0.13. Overall, all the results obtained suggested that NBAC:Ce 3+, Tb 3+ could be a promising option for n‐UV pumped phosphors. Abstract : Color‐tunable phosphors with good thermal stability were synthesized via the construction of Ce 3+ and Tb 3+ co‐doped NaBa4 (AlB4 O9 )2 Cl3